Penerapan PHBS Covid-19 dengan Inovasi Teknologi Aci Telor di Pondok Pesantren Zam-Zam - Adhi, M. Hanif Prasetya; Endiyono, Endiyono (Empowerment : Jurnal Pengabdian Masyarakat, 2021)
COVID-19 is a new type of disease caused by infection with the Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCOV-2). From its initial appearance at the end of 2019 until May 20, 2020, this disease has infected 4,789,205 people and caused the death of 318,789 people worldwide. In Banyumas, there were more than 250 positive Islamic boarding schools students, resulting in a cluster of Islamic boarding schools, in October 2020, the total number of students who were confirmed to be Covid-19 was 722 people. Learning activities are carried out face-to-face, so that as a consideration for determining the location of service, even though there are hand washing facilities, the teacher still has to supervise all students to wash their hands. This shows the low awareness of students about the transmission of Covid-19. Students really need assistance in implementing PHBS to break the transmission of the virus. Promotive, preventive, demonstration, and appropriate technology for ACI TELOR which has been HAKI is expected to be able to increase the adherence of Islamic boarding school students to the health program. The results of this service show that promotive actions accompanied by ACI TELOR innovation increase the interest of teachers and students in complying with health procedures and minimizing virus transmission. The impact of this service is to increase teacher and student compliance with the Covid-19 health protocol so that it is expected to be a behavior that can be applied continuously.